Association between cardiometabolic risk factors and dietary nutrient intakes in Chinese school-aged children: a cross-sectional study. (October 2015) - Unknown
Abstract: Background: A substantial increase in nutrition-related non-communicable diseases has taken place concomitantly with the Chinese nutrition transition. Our study focused on school-aged Chinese children to investigate the prevalence of cardiometabolic risk factors and their association with specific dietary factors. Methods: We included 663 children of 7–12 years who participated in the 2009 China Health and Nutrition Survey. Dietary intake and detailed individual and household data were obtained by trained interviewers during home visits. Anthropometric measures, blood pressure, and fasting blood samples were obtained at local clinics. Logistic regression models were used to investigate the association of nutrient intakes with each cardiometabolic risk factor, adjusting for age, sex, physical activity, area of residence, and household income. Survey instruments, protocols, and informed consent were approved by the institutional review committee of the University of North Carolina at Chapel Hill, NC, USA; the National Institute for Nutrition and Health, Chinese Center for Disease Control and Prevention; and the China–Japan Friendship Hospital, Ministry of Health. Findings: 19% of children had prehypertension and 14% had hypertension. A significant difference in high fasting glucose/glycated haemoglobin (HbA1c) concentrations (fasting glucose ≥100 mg/dL and HbA1c ≥5·7%) was reported between children from urban and rural areas (37% vs 23%; p=0·011), and between children from high-income and low-income households (30% vs 20%; p=0·047). More than 50% of participants had predyslipidemia (ie, at least one lipid measurement above borderline lipid cutoff points), and 21% of children had dyslipidemia. Logistic regression analysis—adjusted by sex, age, physical activity, area of residence, and household income—showed that higher total daily energy intake was associated with a greater likelihood of having pre-hypertension (odds ratio [OR] 1·81 [95% CI 1·03–3·18]; p=0·039), higher total sugar intake was associated with a higher likelihood of hypertension (3·59 [1·76–7·32]; p<0·0001) and impaired glucose/HbA1c (2·02 [1·09–3·75]; p=0·026), and higher intake of added sugar was associated with hypertension (2·13 [1·11–4·09]; p=0·023) and imparied glucose/HbA1c (2·64 [1·42–4·89]; p=0·002). Interpretation: Childhood cardiometabolic risk is prevalent in urban and rural areas of China and across different socioeconomic backgrounds, although disparities between classes still pervade. Several dietary factors, such as sugar consumption, were significant correlates of cardiometabolic risk. Nutritional education and intervention are needed to reduce sugar intake and improve the health status of Chinese children. Funding: This study used data from the China Health and Nutrition Survey, which is supported by the National Institute for Nutrition and Health (China Center for Disease Control and Prevention), Carolina Population Center (the University of North Carolina at Chapel Hill), and a research grant from the US National Institutes of Health. Data analysis was funded by Nestlé Research Center.